2018
DOI: 10.1536/ihj.17-097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sinus Node Recovery Time after Long-Standing Atrial Fibrillation Termination on the Long-Term Outcome of Catheter Ablation

Abstract: SummaryAtrial electrical and structural remodeling is related to the perpetuation of atrial fibrillation (AF) subsequent to sinus node dysfunction. We investigated the relationship between AF recurrence after catheter ablation and sinus node dysfunction in long-standing persistent AF patients using the sinus node recovery time (SNRT) after defibrillation.Fifty-one consecutive patients who underwent a first ablation for long-standing persistent AF were enrolled. Intracardiac cardioversion was applied before abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…20 A study that used late gadolinium-enhanced magnetic resonance imaging to evaluate atrial fibrosis found that significant LA fibrosis was associated with clinically significant SND that required pacemaker implantation. 22 Furthermore, an investigation of 51 long-standing persistent patients who all underwent their first ablation, reported a recurrence rate of 69% during a 28.4-month follow-up period; 23 in this study, a longer SNRT and a larger LA volume were shown to be independent predictors of AF recurrence. The present study found that CSNRT and LAVI were independent risk factors for PAF recurrence.…”
Section: Discussionsupporting
confidence: 52%
“…20 A study that used late gadolinium-enhanced magnetic resonance imaging to evaluate atrial fibrosis found that significant LA fibrosis was associated with clinically significant SND that required pacemaker implantation. 22 Furthermore, an investigation of 51 long-standing persistent patients who all underwent their first ablation, reported a recurrence rate of 69% during a 28.4-month follow-up period; 23 in this study, a longer SNRT and a larger LA volume were shown to be independent predictors of AF recurrence. The present study found that CSNRT and LAVI were independent risk factors for PAF recurrence.…”
Section: Discussionsupporting
confidence: 52%
“…SNRT, reflecting the function of the sinus node, became longer in an aging mouse model, in parallel with increasing AF inducibility (Luo et al, 2013). Clinical studies have also indicated that a longer SNRT is an indicator of AF recurrence after catheter ablation (Yamaguchi et al, 2018). Both animal and human studies have demonstrated that a lengthy AF duration could affect and diminish the function of the AV node, which would manifest in longer AH and HV intervals (Zhang and Mazgalev, 2012;Sairaku et al, 2016).…”
Section: Llvs Inhibited Electrical Remodeling In the Acute Osa Modelmentioning
confidence: 99%
“…The ablation protocol was performed as described previously. 11,12) All procedures were performed under conscious sedation with propofol and/or dexmedetomidine. During the procedure, the activated clotting time was kept above 300 seconds by heparin after the transseptal puncture.…”
mentioning
confidence: 99%
“…An extensive encircling PVI was performed with a single or double circular catheter method, in which two 20-pole circular-shaped catheters (Lasso, Biosense Webster, Diamond Bar, CA, USA) were placed in the ipsilateral superior and inferior PVs. 11) The ablation catheters were 3.5-mm-tip irrigation catheters (NAVISTAR THERMOCOOL, Biosense Webster) or 4mm-tip irrigation catheters (Safire BLU Duo, St. Jude Medical, St. Paul, MN, USA). From October 2013, a 3.5mm-tip irrigation catheter incorporating contact force (SMART TOUCH, Biosense Webster) was used.…”
mentioning
confidence: 99%